Perlunya Membatasi Periode Jabatan Anggota Dewan Perwakilan Rakyat Daerah di Indonesia - Anita Pertiwi; Tomy Michael (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Representative agencies are one of the most crucial components of national governance that require preventive measures to prevent abuse of power. There are no equal rules governing council office periods such as those of executive and judicial offices, which serve to prevent absolutes and excessive abuse of power. The study was intended to analyze the need for limitation of time served by the DPRD. This study is a normative legal research (normative legal research) or library study by finding legal rules, principles of law, by gathering legal materials, such as law norms, law rules, and law principles. Research has found that in preventing abuse of power in the system of governments, it is by setting a time limit for public officials to take office. By establishing a period of time for their tenure, leaders were required to face changes periodically, so that they could not maintain their rule indefinitely. Through a periodic succession of leaders, there will be opportunities for qualified and competent individuals to contribute to government with the restrictions of tenure, there will be a broader share of opportunities for Indonesian citizens to exercise their constitutional rights and become council members. On the other hand, it also makes it less likely that they will find the space or loopholes to do so.